Natural Degradation Behaviour of a Cyanide Leach Solution Under Laboratory Conditions - Tanriverdi, Mehmet; Mordogan, Hasan; Ipekoglu, Uner (Asian Journal of Chemistry, 2016)
Cyanidation has been employed in the recovery of gold and silver for more than a century. Forms of cyanide in mineral processing tailings include free cyanide (HCN and CN ion) and combined or complex cyanides depending on the mineralogy of the ore. Any cyanide containing effluent can be degraded and detoxified by natural degradation or chemically based destruction methods to prevent environmental contamination. In natural degradation certain chemical, physical and biological mechanisms are known to reduce the cyanide content by 99.9%. In this study, the natural degradation behaviour of free cyanide in the leach solution of Gumushane Mastra gold ore has been investigated under laboratory conditions. It was determined that the concentration of free cyanide in leach solution was reduced about 20 times after 70 days of retention time.